2015
DOI: 10.1108/jpmh-05-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the mental health of recently arrived refugee adults in Western Australia

Abstract: Purpose – The purpose of this paper is to measure the levels of psychological distress in adults entering Western Australia (WA) as refugees through the Australian Humanitarian Programme. To determine if the introduction of mental health screening instruments impacts on the level of referrals for further psychological/psychiatric assessment and treatment. Design/methodology/approach – Participants were 300 consecutive consenting refugee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Lack of healthcare at this age may expose women to pregnancy and obstetric complications after birth. Several studies among Afghans, Somalis, Iraqis and Syrian refugees suggest that women face physical and mental health challenges ( Alemi et al, 2016 ; Bogic, Njoku & Priebe, 2015 ; Gerritsen et al, 2006 ; Ghumman, McCord & Chang, 2016 ; Hassan et al, 2016 ; Lillee, Thambiran & Laugharne, 2015 ; Maximova & Krahn, 2010 ; Taylor et al, 2014 ). A study by Hassan et al (2016) suggested that Syrian women experienced a wide range of mental health problems because of the war and immigration.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of healthcare at this age may expose women to pregnancy and obstetric complications after birth. Several studies among Afghans, Somalis, Iraqis and Syrian refugees suggest that women face physical and mental health challenges ( Alemi et al, 2016 ; Bogic, Njoku & Priebe, 2015 ; Gerritsen et al, 2006 ; Ghumman, McCord & Chang, 2016 ; Hassan et al, 2016 ; Lillee, Thambiran & Laugharne, 2015 ; Maximova & Krahn, 2010 ; Taylor et al, 2014 ). A study by Hassan et al (2016) suggested that Syrian women experienced a wide range of mental health problems because of the war and immigration.…”
Section: Introductionmentioning
confidence: 99%
“…12 To add to these clinical diagnoses refugees have been shown to present with a high rate of probable Post Traumatic Stress Disorder. 13 Once in Australia, refugees are often regionalised where 'structural vulnerabilities and discriminations impact upon physical, mental and social wellbeing, leading to further exclusion, with negative longterm implications' 14 (p. 47). There is a need for compassionate and targeted health policies to assist this large section of our society.…”
mentioning
confidence: 99%
“…However, Leiler et.al reported that levels of PTSD symptoms among refugees were about twice as high as in global general population studies [61]. Lillee et.al found significantly higher PTSD prevalence rates among refugees than among the general population [60].…”
Section: Prevalence Ratesmentioning
confidence: 95%
“…Mental health prevalence rates varied from 35.7% [60] to 55% [59] in the selected refugee population. The country of origin was again found to be a significant mental health determinant and could be a reason for the differences in the reports of prevalence rates of general mental health [64].…”
Section: Prevalence Ratesmentioning
confidence: 99%